Pengaruh Skeptisisme terhadap Konsep World Theology dan Global Theology - Ahmad Saifulloh (Universitas Darussalam Gontor, 2013)
Scepticism, in a socio-historical study of philosophy in the West, appeared to have large considerable portion compared with the theories. Scepticism, here means is making a the point of view caution, suspicion, and not directly justify the theory of truth. With all sorts of implementations it generates in the philosophy discourse, Scepticism has become one of the methods to reach the truth. But in terms of theology, it gives a different effect. Scepticism has made the standard of truth of the religions is not based on the ‘truth claim’ that is essentially owned by each religion anymore. Truth is human subjectivity. ‘World Theology’ concept presented by Wilfred Cantwell Smith, the concept of Global Theology presented by John Hick is two discourses of religious pluralism doctrine which affected by scepticism.